Comparative Analysis of the Financial Performance of Financing Institutions Before and After the Credit Delay Policy - Pambudi, Bryan Akram; Kusumawardhani, Indra; Zuhrohtun, Zuhrohtun (Journal of International Conference Proceedings, 2022)
This study aims to examine differences in the financial performance of the Financial Institutions. The measured financial performance is Non Performing Loan (NPL), Return On Asset (ROA), and Current Ratio. The population in this research is a financial institution listed on the Indonesia Stock Exchange (IDX). The sampling method used purposive sampling technique with the criteria of companies that have businesses in the consumer finance sector and have complete information to process research data. The samples obtained from the use of this technique is 8 companies and 48 observations. The analytical method used is the Wilcoxon/Shapiro-Wilk test to test the hypothesis. The results show that there are significant differences in Non Performing Loan  (NPL), Return On Assets (ROA), and Current Ratios of Financing Institutions before and after credit payment delay policy.